Retroperitoneal Inflammation Detected on FDG PET/CT in Patient on Long-Term Immunotherapy. (1st April 2023) - Khessib, Tasnim; Franc, Benjamin; Yang, Eric; Moradi, Farshad
Abstract: A 68-year-old man with a history of pulmonary adenocarcinoma on maintenance pembrolizumab presented for surveillance imaging. 18 F-FDG PET/CT demonstrated new ill-defined right retroperitoneal and presacral soft tissue stranding with associated FDG uptake suggestive of inflammation. Biopsy results revealed fibroadipose tissue with extensive lymphoplasmacytic inflammation concerning for immunotherapy-related toxicity. The patient was subsequently taken off pembrolizumab, which he had been on for approximately 3 years. Recognition of immunotherapy-related adverse effects and how they can manifest on 18 F-FDG PET/CT is important for prompt cessation of treatment.